Optimalisasi Strategi One Week One Book dalam Pembelajaran Bahasa Indonesia Meningkatkan Minat Baca dan Hasil Belajar pada Peserta Didik Kelas II - Yekti, Wulan Nugroho (Universitas Muhammadiyah Magelang, 2022)
This study aimed to increase the reading interest of class II students at SDN Kemirirejo 1 after the covid-19 pandemic. The research was conducted to resolve the main issue at SDN Kemirirejo 1: the teacher's strategy was not yet optimal for increasing students' interest in reading in learning. The research method used is classroom action research. The subjects of this research are 28 students. The instrument used in the measurement is a questionnaire of reading interest as the main instrument, tests, observations, and interviews as the supporting instrument. The data analysis used was descriptive percentages. This study uses interactional analysis to examine the data quantitatively and qualitatively. The minimum completeness criteria (KKM) for learning outcomes is determined at 70, while the criteria for research success are determined classically at 80%. The results showed an increase in interest and learning outcomes in all cycles. In the pre-cycle, students' interest was obtained with a level of 45%, Indonesian language learning outcomes with an average value of 49, and classical minimum completeness criteria obtained at 40%. In the first cycle, students' interest was obtained at 65%, Indonesian language learning outcomes at 69, and the classical minimum completeness criteria obtained at 67%. In the second cycle, students' interest was obtained with a level of 86% and Indonesian language learning outcomes with 79, and the minimum completeness criteria classically obtained at 100%. There was an increase in reading interest in the first cycle by 20% and in the second cycle by 24%. The increase in learning outcomes has an average increase in learning outcomes of 10 points, with an increase in mastery of 27% in the first cycle, and an average increase of 10 points, with a 21% increase in mastery in the second cycle. In acquiring reading interest and learning outcomes, there is a significant increase in the one week one book strategy in learning Indonesian. Keywords: strategy, reading interest, learning outcomes, Indonesian language